Aroh, Prudentius Emeka, Priestly Celibacy: a Gift and a Commitment (can. 277 § 1). Adaption to Igbo Culture, Nigeria, Rom 2014 (= Tesi Gregoriana, Serie Diritto canonico; 99): [Rezension] - Greiner, Philippe (L' année canonique, 2014)
Vgl. can. 132.1 CIC/1917. Vgl. can. 373 CCEO